A probabilistic study of welding residual stresses distribution and their contribution to the fatigue life - Manai, Asma; Franz von Bock und Polach, Rüdiger Ulrich; Al-Emrani, Mohammad (Engineering failure analysis, 2020)
•Probabilistic study of the shape of welding residual stresses at the weld toe through the thickness direction in both cases.•When welding introduces compressive residual stresses at the surface.•When welding introduces tensile residual stresses at the surface.•Contribution of welding residual stresses to the fatigue life (failure) of the structures.•Prediction of the welding residual stresses shape by knowing only the magnitude of the surface residual stresses. Welding is a joining process that is associated with heating cycles which leads to considerable change in local material microstructure and the formation of high welding Residual stresses (RS) in the welded joint. Residual stresses can have a detrimental effect on the fatigue strength of welded joints. In this paper, previously published data from measurements of residual stresses in various types of welded joints are compiled. In total, more than 100 test results are studied covering steels with yield strengths between 307 MPa and 1050 MPa in different welded details (butt joints, longitudinal and transverse attachments, cruciform joints, as well as K-joints) with varying thicknesses. The collected data is used to study the distribution of welding residual stresses (regardless of the welding parameters) at weld toe and through the thickness of the welded plate. Probabilistic analysis is then used to arrive at a model that represents the value and distribution of residual stresses in welded joints. This model is used to predict and explain the scatter in fatigue test data from recent fatigue testing of welded samples.